Diversity and Bias through Receptor–Receptor Interactions in GPCR Heteroreceptor Complexes. Focus on Examples from Dopamine D2 Receptor Heteromerization - Fuxe, Kjell; Tarakanov, Alexander; Romero Fernandez, Wilber; Ferraro, Luca; Tanganelli, Sergio; Filip, Malgorzata; Agnati, Luigi F.; Garriga, Pere; Diaz-Cabiale, Zaida; Borroto-Escuela, Dasiel O. (Frontiers in Endocrinology, 2014)
Allosteric receptor-receptor interactions in GPCR heteromers appeared to introduce an intermolecular allosteric mechanism contributing to the diversity and bias in the protomers. Examples of dopamine D2R heteromerization are given to show how such allosteric mechanisms significantly change the receptor protomer repertoire leading to diversity and biased recognition and signaling. In 1980ies and 1990ies it was shown that neurotensin through selective antagonistic NTR-D2likeR interactions increased the diversity of DA signalling by reducing D2R mediated dopamine signalling over D1R mediated dopamine signalling. Furthermore, D2R protomer appeared to bias the specificity of the NTR orthosteric binding site towards neuromedin N vs neurotensin in the heteroreceptor complex. Complex CCK2R-D1R-D2R interactions in possible heteroreceptor complexes were also demonstrated further increasing receptor diversity. In D2R-5-HT2AR heteroreceptor complexes the hallucinogenic 5-HT2AR agonists LSD and DOI were recently found to exert a biased agonist action on the orthosteric site of the 5-HT2AR protomer leading to the development of an active conformational state different from the one produced by 5-HT. Furthermore, as recently demonstrated allosteric A2A-D2R receptor-receptor interaction brought about not only a reduced affinity of the D2R agonist binding site but also a biased modulation of the D2R protomer signalling in A2A-D2R heteroreceptor complexes. A conformational state of the D2R was induced which moved away from Gi/o signaling and instead favoured b-arrestin2 mediated signalling. These examples on allosteric receptor-receptor interactions obtained over several decades serve to illustrate the significant increase in diversity and biased recognition and signaling that develop through such mechanisms.